Modelo Pedagógico de la escuela nueva en el desarrollo socio emocional de los niños de 3 a 5 años - Laverde Reinoso, Jenifer Magaly (2022)
This project focuses on the topic, "Pedagogical model of the New School in the socio-emotional development of children from 3 to 5 years old" of the Semillitas Initial Educational Center "César Francisco Naranjo Rumazo" and the Educational Unit "Belisario Quevedo" of the Pujilí Canton, with the purpose of satisfying the socio-educational needs and achieving an active participation among authorities, teachers, parents and students, through a diagnosis of its application in educational processes. To do that, the main general objective was to determine the incidence of the pedagogical model of the New School in the socio-emotional development in order to improve the teaching and learning process of children from 3 to 5 years old. Therefore, the project was carried out using an explanatory and descriptive research, since it allowed us to carry forward an analysis and detailed description of the variables of the proposed topic under study. Furthermore, it has a qualitative approach that allowed collecting information to be later analyzed, as well as a quantitative approach because the information was presented in graphics and statistical analysis, which helped to know the current situation of the application of this model. These were possible thank to the application of the survey and interview techniques, which revealed that at present, the pedagogical model of the New School is not applied due to the lack of knowledge of the methodologies as such. Additionally, it was found that they do not develop the socioemotional skills in totality; educational institutions are also governed by the provisions of the Ministry of Education. It should be noted that the contributions provided by this research will be reflected when future researchers develop the proposal as a solution to the problem identified, so they will be able to use the information collected; the impacts that will be generated are of character, social, environmental, technical, and economic.